Among-breed estimates of heritability for birth weight, weaning weight, and mature cow weight - Andries, K.M.; Schalles, R.R.; Franke, D.E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Data from a rotational crossbreeding study was used to calculate among-breed heritabilities of birth weight (BWT), weaning weight (WWT), and mature cow weight at 5 years of age. The among-breed estimates were higher than previous within-breed estimates because of the inclusion of genetic differences between breeds. Maternal effects for BWT and WWT also were calculated. These estimates allow for comparisons among breeds and for the eventual calculation of EPDs for hybrid cattle.
Keywords: Beef; Heritability; Birth weight; Weaning weight; Cow weight